Nutrition Education Improves Knowledge of Iron and Iron-Rich Food Intake Practices among Young Adolescents: A Nonrandomized Controlled Trial - Michael Akenteng Wiafe; Charles Apprey; Reginald Adjetey Annan (International Journal of Food Science)
Introduction. Nutrition education targeting adolescents’ health has the potential to enhance their well-being into adulthood. This study assessed the impact of nutrition education on the knowledge of iron and iron-rich food intake practices of adolescents living in rural communities in Ghana. Method. An intervention study was conducted among 137 adolescents; 69 were assigned to the intervention group and 68 to the control group. Participants and guardians in the intervention group were involved in the nutrition education programme for six months. Participants in both groups completed sociodemographic, knowledge of iron, and iron-rich food intake practice questionnaires at pre- and postintervention. Data were analyzed by chi-square and t-tests. Results. At postintervention, the mean knowledge score (p<0.05) in the intervention group and control group was 5.3±1.7 and 3.9±1.9, respectively. Interventions (76%) and controls (46%) had good knowledge status. The mean knowledge score of participants with good knowledge status in the intervention group was 6.1±0.8 (p<0.05), and the control group was 5.6±0.7 (p<0.05). Forty-two percent of participants in the interventions and 26% in the controls had good food intake status. Participants with good food intake status had mean food intake scores of 3.2±0.4 (p<0.05) and 3.8±0.7 (p<0.05) for the intervention and control groups, respectively. Both groups increased and had the same mean food intake score (1.5±1.4, p>0.05), however, relatively higher in the intervention group. Conclusion. Nutrition education improved the knowledge of iron and iron-rich food intake practices of participants in the intervention group compared to the control group. Nutrition education should be a critical component in the management and prevention of micronutrient deficiency in adolescents.